Using precise word timing information improves decoding accuracy in a multiband-accelerated multimodal reading experiment. Issue 3 (18th May 2016) - Vu, An T.; Phillips, Jeffrey S.; Kay, Kendrick; Phillips, Matthew E.; Johnson, Matthew R.; Shinkareva, Svetlana V.; Tubridy, Shannon; Millin, Rachel; Grossman, Murray; Gureckis, Todd; Bhattacharyya, Rajan; Yacoub, Essa
ABSTRACT: The blood-oxygen-level-dependent (BOLD) signal measured in functional magnetic resonance imaging (fMRI) experiments is generally regarded as sluggish and poorly suited for probing neural function at the rapid timescales involved in sentence comprehension. However, recent studies have shown the value of acquiring data with very short repetition times (TRs), not merely in terms of improvements in contrast to noise ratio (CNR) through averaging, but also in terms of additional fine-grained temporal information. Using multiband-accelerated fMRI, we achieved whole-brain scans at 3-mm resolution with a TR of just 500 ms at both 3T and 7T field strengths. By taking advantage of word timing information, we found that word decoding accuracy across two separate sets of scan sessions improved significantly, with better overall performance at 7T than at 3T. The effect of TR was also investigated; we found that substantial word timing information can be extracted using fast TRs, with diminishing benefits beyond TRs of 1000 ms.